Analisis Wacana Pemberitaan Isu Kenaikan Harga Rokok di CNN Indonesia Periode Agustus 2016 - Pratiwi, Windy; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
This research was conducted to find out the discourse presented by CNN Indonesia in announcing the issue of cigarette price increase in August 2016. This qualitative research use discourse analysis method of Teun A. Van Djik. The results of this research indicate that CNN Indonesia raised the discourse, which is “Supporting the Increase of Cigarette Prices”. The discourse arises through the following process: First, the gatekeeper selected the information. Second, the information that has been selected appears as a media agenda. Third, the media agenda establishes a public agenda and policy agenda, in which a public agenda appears to provide public new perception and the policy agenda is delivered to the government to immediately reinforce cigarette regulation in Indonesia. Keywords : CNN Indonesia, Discourse Analysis of Teun A. Van Djik, News of Rising Cigarette Prices, News Text Analysis.